A Fluorescence Switching Sensor for Sensitive and Selective Detections of Cyanide and Ferricyanide Using Mercuric Cation-Graphene Quantum Dots - Niradchada Kongsanan; Nipaporn Pimsin; Chayanee Keawprom; Phitchan Sricharoen; Yonrapach Areerob; Prawit Nuengmatcha; Won-Chun Oh; Saksit Chanthai; Nunticha Limchoowong (My University, 2021)
This study aims to use graphene quantum dots (GQDs) as a fluorescence switching sensor (turn on-off) for the simultaneous detection of cyanide (CN
Keywords: Ferricyanide; Carbon and Quantum Dots Applications